2020
DOI: 10.1136/bmjspcare-2019-002076
|View full text |Cite
|
Sign up to set email alerts
|

Psychological concerns of Indian women with breast cancer in different national contexts: a systematic review and mixed-methods synthesis

Abstract: BackgroundBreast cancer is becoming the most common cancer among women of Indian origin. However, little is known about the psychological impact of the disease and its treatment among this population.AimTo improve understanding of psychological symptoms among Indian women with breast cancer.DesignThis is a systematic literature review and critical interpretive synthesis. Medical Subject Headings(MeSH) terms and keywords for breast cancer, psychological symptoms and treatment were used to search databases from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 46 publications
2
6
0
Order By: Relevance
“…The collectivist family [33] was considered as strong sources of support. However, consistent with our previous work [2,3], a "two-edged sword" was described whereby some women felt "unsupported" and worried particularly about "spousal abandonment", aggravated by a cultural reluctance of Indian men to show emotion. Similarly, faith practice is described as a major source of strength and resilience consistent in various other cultures [34,35].…”
Section: Agreementsupporting
confidence: 86%
See 3 more Smart Citations
“…The collectivist family [33] was considered as strong sources of support. However, consistent with our previous work [2,3], a "two-edged sword" was described whereby some women felt "unsupported" and worried particularly about "spousal abandonment", aggravated by a cultural reluctance of Indian men to show emotion. Similarly, faith practice is described as a major source of strength and resilience consistent in various other cultures [34,35].…”
Section: Agreementsupporting
confidence: 86%
“…Breast cancer is the most prevalent cancer among women globally. Psychological distress is common and is related to the impact of this disease on the woman's role in the family and wider community [1][2][3]. A recent systematic review [2] found that Indian women with breast cancer, living in India or as immigrants in Canada experienced distress, both ameliorated and exacerbated by similar cultural issues.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent systematic review [5] found that Indian women living in India or as immigrants in Canada experienced a range of psychological distresses both ameliorated and exacerbated by cultural issues personally, within the family, within their community, and in the context of faith. The cultural issues identified were similar for the women irrespective of the country studied.…”
Section: Introductionmentioning
confidence: 99%